A Review of the Possible Effects of Physical Activity on Low-Back Pain - Edward J Sinkule (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Objective: Low back pain (LBP) represents the most prevalent and costly repercussion from musculoskeletal injury in the work place. This review examines the earlier and current research reported on the significance of physical activity on musculoskeletal injuries and LBP, the benefits and limitations of therapeutic exercise, and the potential features of various exercise modalities that may contribute to the secondary and tertiary prevention of low-back pain.  Methods: A search was performed using MEDLINE to identify original studies published in English from January 1990 to December 2013. Physical activity in the form of aerobic, muscle strengthening, flexibility, and occupational (labor) activities among working adults (18 - 65 years of age) alone and with other non-surgical therapies were selected. A hand-searched collection from a personal literature library also was used. Results: Fifteen studies met the inclusion criteria, addressing aerobic exercise (n=4), muscle strengthening exercise (n=3), combination of aerobic, muscle strengthening, and flexibility exercises (n=5), and occupational labor/exercise (n=3). The investigations generally supported the benefits of programmed and structured exercise alone and with other therapies for the treatment of LBP. Conclusions: Given the physical and financial burden to treat LBP, this issue remains a great public health importance. With the burden on society from LBP and the prevalence of the disorder among populations, research from physical activity on LBP has produced varied results without a specific type of exercise that results in resolved LBP better than most. Most agree that some activity is better than none, but no one activity is better than the others when the multifactorial etiology of LBP remains inconsistent. Isolating the vertebrae that causes the LBP would be beneficial for participant selection with future research. Different forms of pathological evidence or combinations of pathological measurements may help to establish proof of beneficial exercise or a combination of exercise therapies.